2016
DOI: 10.1073/pnas.1605881113
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and function of Neandertal and modern human ear ossicles

Abstract: The diminutive middle ear ossicles (malleus, incus, stapes) housed in the tympanic cavity of the temporal bone play an important role in audition. The few known ossicles of Neandertals are distinctly different from those of anatomically modern humans (AMHs), despite the close relationship between both human species. Although not mutually exclusive, these differences may affect hearing capacity or could reflect covariation with the surrounding temporal bone. Until now, detailed comparisons were hampered by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 69 publications
6
35
0
Order By: Relevance
“…biorxiv.org/content/early/2017/10/03/106955]), breathing control, and acoustic sensitivity (audiograms) involved in modern speech. Since then, there is better evidence that the Neanderthal cochlear volume and audition were similar to modern humans and different from the chimpanzees [67], that despite differences in the morphology of the ear ossicles (probably due to differences in cranium) they were functionally very similar probably due to selective pressures for the maintenance of the same auditory profile [68 ], while the biomechanical modeling of the Kebara 2 Neanderthal hyoid showed that it is extremely similar to the modern human one in more than just shape [69 ].…”
Section: Inferences Concerning Language and Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…biorxiv.org/content/early/2017/10/03/106955]), breathing control, and acoustic sensitivity (audiograms) involved in modern speech. Since then, there is better evidence that the Neanderthal cochlear volume and audition were similar to modern humans and different from the chimpanzees [67], that despite differences in the morphology of the ear ossicles (probably due to differences in cranium) they were functionally very similar probably due to selective pressures for the maintenance of the same auditory profile [68 ], while the biomechanical modeling of the Kebara 2 Neanderthal hyoid showed that it is extremely similar to the modern human one in more than just shape [69 ].…”
Section: Inferences Concerning Language and Speechmentioning
confidence: 99%
“…biorxiv.org/content/early/2017/10/03/106955]), breathing control, and acoustic sensitivity (audiograms) involved in modern speech. Since then, there is better evidence that the Neanderthal cochlear volume and audition were similar to modern humans and different from the chimpanzees [67], that despite differences in the morphology of the ear ossicles (probably due to differences in cranium) they were functionally very similar probably due to selective pressures for the maintenance of the same auditory profile [68 ], while the biomechanical modeling of the Kebara 2 Neanderthal hyoid showed that it is extremely similar to the modern human one in more than just shape [69 ].Neanderthals had elaborate cultural adaptations that were virtually identical to AMH (until the latter developed the Upper Paleolithic toolkit after the demise of the Neanderthals), they flexibly adapted to their ecologies, buried their dead (apparently with mortuary ceremonies), built large structures, penetrated deeply into caves, and seem to have adorned themselves with drilled beads and feathers. They inhabited a climatic range (from Arctic to Mediterranean) requiring the extended ability to use culture as a buffer for ecological adaptation, and they interacted repeatedly with AMH over tens of thousands of years, exchanging genes, parasites and culture.…”
mentioning
confidence: 99%
“…This potentially autapomorphic configuration may have impacted the efficiency of middle ear aeration and hence, disease susceptibility during their childhood years. Evidence of osteological pathology congruent with OM has been reported in many Neanderthal specimens with perhaps the most compelling observation by Stoessel et al (2016) Quina H5, Le Moustier 1, Pech de l'Azé 1). All the mallei and incudes recovered (N = 17) exhibited substantial amounts of pitting lesions similar to such erosions found in modern Fig.…”
Section: Discussionmentioning
confidence: 85%
“…All the mallei and incudes recovered (N = 17) exhibited substantial amounts of pitting lesions similar to such erosions found in modern patients with chronic episodes of OM (Sade et al, ). Stoessel et al () also reported additional evidence of OM within the tympanic bone of La Quina H5. A study of Neanderthal ossicles from Amud, Israel by Quam and Rak () also confirmed the presence of pitting lesions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation